Physical Activities of Diabetes Mellitus Patients at Binjai Estate Health Center in 2020 - Wirda Faswita (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2021)
Diabetes mellitus has increased from 8.4 million in 2000 to around 21.3 million in 2030 in Indonesia. The purpose of this study was to describe the quality of life picture of type 2 diabetes mellitus at Binjai Estate Health Center. This type of research is a quantitative research, with a descriptive design with univariate analysis. Researchers took samples with non probability sampling on 20 people with Diabetes Mellitus. The results of the study based on the characteristics of the majority of respondents aged 51-59 years were 11 people (55%), 11 people (55%) female gender, 6 people (30%) at the junior high school level, who worked as housewives. as many as 11 people (55%), long suffering from type 2 diabetes mellitus for 2-5 years as many as 9 people (45%), blood sugar levels when diabetes mellitus patients who were categorized as abnormal (≥ 200 mg / dL) were 15 people ( 75%), 10 people (50%) light physical activity. It is hoped that further researchers will carry out related research on the increase in physical activity of patients with Type 2 diabetes mellitus.Keywords: Physical Activity, Diabetes Mellitus Type 2